IoT based temperature and humidity monitoring framework - Rafizah Ab Rahman; Ummi Raba'ah Hashim; Sabrina Ahmad (Institute of Advanced Engineering and Science, 2020)
This study explored the use of Internet of Things (IoT) in monitoring the temperature and humidity of a data centre in real-time using a simple monitoring system to determine the relationship and difference between temperature and humidity with respect to the different locations of measurements. The development of temperature and humidity monitoring system was accomplished using the proposed framework and has been deployed at the data centre of Politeknik Muadzam Shah, where the readings were recorded and sent to an IoT platform of AT and T M2X to be stored. The data was then retrieved and analysed showing that there was a significant difference in temperature and humidity measured at different locations. X The monitoring system was also successful in detecting extreme changes in temperature and humidity and automatically send a notification to IT personnel via e-mail, short messaging service (SMS) and mobile push notification for further action.